1.9 µm hybrid silicon/III‐V semiconductor laser. Issue 10 (1st May 2013) - Dong, P.; Hu, T.‐C.; Zhang, L.; Dinu, M.; Kopf, R.; Tate, A.; Buhl, L.; Neilson, D.T.; Luo, X.; Liow, T.‐Y.; Lo, G.‐Q.; Chen, Y.‐K.
Abstract : A 1.9 µm hybrid silicon/III‐V laser based on a wafer bonding technique is reported. The gain materials are InGaAs multiple quantum wells grown on InP substrate, with strain compensation between barriers and wells. The III‐V wafer is bonded to a silicon‐on‐insulator wafer with processed silicon waveguides and transition tapers. Laser emission with a threshold current of 95 mA at room temperature and 45 mA at 5 °C is demonstrated.